1994
DOI: 10.1007/bf01870934
|View full text |Cite
|
Sign up to set email alerts
|

The preservation of some oral liquid preparations

Abstract: Chloroform should be considered as an obsolete preservative for pharmaceutical preparations, because of its toxicological implications and its physical instability. The effectiveness of possible alternatives for chloroform in three oral liquid pharmaceutical preparations was investigated, using a microbiological challenge test. Magnesium trisilicate mixture (British Pharmacopoeia) can be adequately preserved with methylparaben (2 g/l). Only insignificant amounts of methylparaben were absorbed by the solids pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…On the other hand, oral morphine with Simple Syrup requires the use of chloroform water as a preservative. Chloroform water has been an obsolete preservative for many years ago due to the concern of safety profile when used in certain populations [9], especially among the paediatrics population. Hence, the use of X-Temp ® OSS in the production of oral morphine solution provides a safer preparation for clinical use in broader demographics of patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, oral morphine with Simple Syrup requires the use of chloroform water as a preservative. Chloroform water has been an obsolete preservative for many years ago due to the concern of safety profile when used in certain populations [9], especially among the paediatrics population. Hence, the use of X-Temp ® OSS in the production of oral morphine solution provides a safer preparation for clinical use in broader demographics of patients.…”
Section: Discussionmentioning
confidence: 99%
“…have been used a drug of colic, malaria, diuretic, fever, and skin disease [2]. Modern pharmacological investigations indicated that the extract of P. fel-terrae Lour exerts diuretic, antipyretic, hepatoprotective, cardioprotective, antidiabetic, antioxidant, anti-inflammatory, anthelmintic, and analgesic activities [3], [4], [5], [6], [7], [8], [9], [10], [11]. Moreover, P. fel-terrae inhibits hepatitis B (HB) e-antigen excreted by HepG2 2215 cell lines, suggesting having anti-HB virus activity [12].…”
Section: Introductionmentioning
confidence: 99%
“…Chloroform is now considered an obsolete preservative for pharmaceutical preparations due to its toxicity and physical instability. 2 The warfarin formulations have a pH above 5.0 making benzoic acid an unsuitable preservative. An unreferenced report of the incompatibility of warfarin with hydroxybenzoates resulted in the historic use of concentrated chloroform water.…”
Section: Introductionmentioning
confidence: 99%